Effect of terrain on electromagnetic propagation in urban environments on the Andean region, using the COST231-Walfisch-Ikegami model and GIS planning tools (2003)
This paper includes some results from a research project for the development of an electromagnetic propagation algorithm considering the influence of mountain terrain in UHF (300 MHz-3 GHz) band for wireless communications systems (i.e. 800-900 MHz in DAMPS/US-TDMA/IS-136 and GSM standard). The COST231-Walfisch-Ikegami (1988, 1991) model used in this work has been shown, together with Geographic Information System (GIS) and prediction tools for mobile propagation, to facilitate propagation studies, coverage analysis and analysis of main factors for cell planning in mobile systems. The basic concepts used to design the algorithm, the parameters used in measurements and results analysis in order to verify its applicability in cellular coverage prediction are described. Measurements have been done initially in Bucaramanga, a city located in the Andean Mountain system, for IS-136 band system. Coverage predictions have been done using a locally modified version of CellView, a GIS based Planning tool developed by the Universidad Politecnica de Valencia, while for the measurements a portable monitoring unit (i.e. Miniport Receiver EB200-Rohde&Schwarz from 10 kHz-3 GHz) was used.